The Effect of Recognition and Appreciation on Employee Motivation and Performance - Un Dini Imran; Muhammad Faathir Ghazwan; Firmansyah Firmansyah (STIE Amkop Makassar, 2025)
This study examines the dual effects of recognition and appreciation on employee motivation and performance. It aims to address how these elements influence workplace dynamics and explore practical strategies for implementing sustainable recognition and appreciation systems across various organizational contexts. Utilizing a qualitative systematic literature review approach, this research synthesizes findings from recent studies to analyze the roles of recognition and appreciation. The study integrates theoretical frameworks such as Herzberg’s Two-Factor Theory and Self-Determination Theory to understand their impact on extrinsic and intrinsic motivation comprehensively. The study reveals that recognition significantly enhances extrinsic motivation by validating employees’ contributions, fostering a sense of achievement, and encouraging task completion. Appreciation strengthens intrinsic motivation by fulfilling psychological needs for relatedness, competence, and autonomy, enhancing emotional engagement and long-term commitment. The synergistic integration of recognition and appreciation optimizes employee performance, increasing engagement, reducing turnover, and promoting organizational citizenship behaviors. The findings emphasize the importance of tailoring these strategies to align with organizational and employee needs while leveraging technology for real-time and accessible implementation. This study offers practical and managerial insights by recommending flexible, technology-based systems to integrate recognition and appreciation into organizational policies. The findings support the development of inclusive and innovative workplace cultures that enhance productivity and employee satisfaction. Furthermore, the research highlights opportunities for future empirical studies to validate these findings and adapt strategies to evolving workplace trends, such as remote and hybrid environments.